Real-Life Situation Of Bile Duct Injury Management: Challenges And Lessons From A Tertiary Care Center - Pramana, Triyanta Yuli; Adhyaksari, Apriliana; Lee, See Young; Ratanachu-ek, Thawee; Ranty, Stefanus Satrio; Prasetyo, Ari; Darmayani, Aritantri; Prasetyo, Didik; Notonugroho, Anung (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: Bile duct injury (BDI) is a serious complication of cholecystectomy, particularly with the widespread adoption of laparoscopic cholecystectomy (LC). Currently, a wide spectrum of multidisciplinary interventions with different degrees of invasiveness is indicated for BDI management. This study evaluates reallife clinical experiences in managing post-cholecystectomy BDIs in Central Java, Indonesia. We aim to discuss the prevention of BDI further and find out the most effective management and timing of interventions for BDI based on these analyses.Methods: Twenty-seven cases with iatrogenic BDI following cholecystectomy were classified according to BDI Strasberg classification, repair procedures, mortality and success rate procedures, onset of BDI, and timing of repair procedures. The correlation analyses were performed using the Contingency Coefficient Correlation Test.Results: Of the 27 patients, BDIs were detected in 33.3% of patients within two weeks of surgery. Major BDIs (Strasberg E) often required biliodigestive surgery, with variable outcomes. The overall mortality rate was 29.6%, mainly due to biliary sepsis. ERCP success was significantly associated with less severe BDI (p=0.018). This study stated that the type of previous cholecystectomy, timing of BDI diagnosis, and duration of BDI to repair procedures did not statistically influence mortality (p=0.822, p=0.551, p=0.958, respectively).Conclusion: Prevention of BDI is paramount, emphasizing surgical training, careful patient selection, and the critical view of safety technique. Early detection, multidisciplinary management tailored to the injury’s severity improve outcomes. While minimally invasive approaches are preferred for minor BDIs, major injuries necessitate surgical intervention by experienced hepatobiliary surgeons.